Reproductive habitat mismatch influences chytrid infection dynamics in a tropical amphibian community - Gilbert, Neil A.; Bell, Rayna C.; Catenazzi, Alessandro; Martins, Renato A.; Buttimer, Shannon; Neely, Wesley J.; Lambertini, Carolina; Calderon, Veronica Saenz; Haddad, Célio F.B. [UNESP]; Becker, C. Guilherme; DiRenzo, Graziella V. (Elsevier, 2025)
Batrachochytrium dendrobatidis (Bd) has been decimating amphibian populations globally; previous work indicates that infection risk increases with moisture and thermal mismatch from a host’s optimum. We hypothesized that, in addition to these abiotic influences, mismatch of hosts from their reproductive habitat heightens infection risk via exposure and/or susceptibility mechanisms. We evaluated this “reproductive habitat mismatch hypothesis” by quantifying the interplay of host breeding mode, habitat, and rainfall on Bd infection dynamics using two years of frog survey data—including swab data for 3427 captures representing 44 species—from Brazil’s Atlantic Forest. We modeled infection prevalence, infection intensity, and the number of frogs captured as a function of rainfall, reproductive mode (aquatic or terrestrial), and habitat (aquatic or terrestrial) using hierarchical models. High rainfall was associated with increases in infection prevalence and infection intensity; however, these increases were particularly apparent for species in habitats that were mismatched from the species’ reproductive habitat. Tropical regions experiencing increases in precipitation will likely see higher Bd risk, and our results indicate that such increases in rainfall will be particularly problematic for species that are forced to move from their reproductive habitats by factors such as habitat loss or thermal stress.